Response Surface Optimization of Diltiazem HCl Gastric Floating Matrix Tablets (Asian Journal of Pharmaceutics (AJP), 2020)
Objective: The objective of the present research work was to formulate and optimize the hydroxyethyl cellulose (HEC) based gastric floating matrix tablets (GFMT) of diltiazem HCl by employing a three factor, three levels statistical design, namely, Box-Behnken design. Materials and Methods: Optimization studies were carried out using Box-Behnken statistical design with three factors, three levels, and 15 runs. Selected independent variables include HEC quantity (X1), %w/w of sodium bicarbonate (X2), and %w/w of Pharmatose (lactose monohydrate) (X3). Cumulative percent drug released at 12 h was selected as dependent variable (Y). Tablets were evaluated for in vitro buoyancy characteristics, in vitro drug release and other tablet characteristics. Results and Discussion: The GFMT’s of diltiazem HCl prepared with HEC fulfilled all the requirements of tablets. Floating lag times for all the prepared formulations were found to be in the range of 156–2040 s. The obtained optimum values of the independent test variables are; 93.50 mg quantity of HEC (X1), 11.47% w/w of sodium bicarbonate (X2), and 10.40% w/w of Pharmatose (lactose monohydrate) (X3). The model predicts that the formulation with 100% drug release in 12±1 h can be obtained using the above optimum concentrations. Optimized formulation DNAso showed a floating lag time of 405 s. Drug release from DNAs (optimized formulation) and Dilzem SR (commercial sustained release formulation) followed zero-order release kinetics with diffusion mechanism. Conclusion: Results demonstrated that significance of Box-Behnken statistical design in the optimization of critical variables of gastric floating matrix tablets of diltiazem HCl for achieving desired in vitro buoyancy characteristics and in vitro drug release characteristics.